Electrochemical direct air capture of CO2 using neutral red as reversible redox-active material - Hyowon Seo; T. Alan Hatton (Nature Communications, 2023)
Electrochemical direct air capture (DAC) of CO2 requires air-stable redox-active materials. Here, the authors present an electrochemical DAC using air-stable redox couple of neutral red with a minimum energy requirement of 65 kJe/molCO2.